2019
DOI: 10.3389/fphar.2019.01308
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-Catenin Pathway-Regulated Fibromodulin Expression Is Crucial for Breast Cancer Metastasis and Inhibited by Aspirin

Abstract: Emerging evidence suggests that fibromodulin (FMOD), an extracellular matrix protein, is associated with cancer, and yet little is known about the regulation of FMOD expression and its role in cancer metastasis. Aspirin, a classic anti-inflammatory drug, has been indicated to offer anticancer benefits, but its action targets and mechanisms remain obscure. In the present study using cell lines, animal model and database analysis, we show that FMOD is crucial for breast cancer cell migration and invasion (BCCMI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…Wnt signaling proteins interact with the frizzled family of cell-surface receptors and activate the proteins of the disheveled family, which in turn results in the inhibition of proteolytic degradation of β-catenin. Subsequently, stabilized β-catenin is translocated into the nucleus, leading to the transcription of target genes such as C-Myc and Cyclin D1, which are involved in determining cell migration, cytoskeletal activity, cell polarity, and cellular differentiation ( 39 , 40 ). Recently, the overexpression of Wnt pathway has been observed in breast, lung, and hematopoietic malignancies and contributes to tumor recurrence ( 41 ).…”
Section: Chemoresistance Mechanisms In Brcamentioning
confidence: 99%
“…Wnt signaling proteins interact with the frizzled family of cell-surface receptors and activate the proteins of the disheveled family, which in turn results in the inhibition of proteolytic degradation of β-catenin. Subsequently, stabilized β-catenin is translocated into the nucleus, leading to the transcription of target genes such as C-Myc and Cyclin D1, which are involved in determining cell migration, cytoskeletal activity, cell polarity, and cellular differentiation ( 39 , 40 ). Recently, the overexpression of Wnt pathway has been observed in breast, lung, and hematopoietic malignancies and contributes to tumor recurrence ( 41 ).…”
Section: Chemoresistance Mechanisms In Brcamentioning
confidence: 99%
“…Khan et al . showed that in human breast cancer patients, the Wnt/β-catenin signaling is highly activated, suggesting poor prognosis in patients with activated Wnt/β-catenin signaling ( 12 ). A study has also shown that the Wnt/β-catenin signaling is also highly active in CMGTs ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Aspirin in a combination with the cisplatin inhibit the migration of non-small cell lung carcinoma stem-like cells by targeting mTOR-Akt axis ( 11 ). And Khan FU using cell lines, animal model and database analysis shows that Aspirin inhibits breast cancer cell migration and invasion by attenuating Wnt/β-catenin signaling and suppressing fibromodulin expression ( 12 ). On the other hand, in osteosarcoma cell lines Aspirin reduced cell viability in a dose- and time-dependent manner ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of Dickkopf-related protein (DKK)-1 (inhibitor of Wnt) and ICG-001 (inhibitor of β-catenin) could attenuate peritoneal angiogenesis and reduce VEGF [ 11 ]. Interestingly, HDAC6 was reported to regulate β-catenin by deacetylation, leading to β-catenin phosphorylation and activation of downstream signal molecules [ 46 ]. Further research indicated that HDAC6-induced β-catenin deacetylation (K345) is essential for Wnt signal transduction [ 47 ].…”
Section: Discussionmentioning
confidence: 99%